Fabrication of Carbonaceous-Modified Halloysite Nanotubes for the Removal of Metal Ions from Aqueous Solution - Meryemoğlu, Bahar; Özsel, Burcak; Niş, Berna (My University, 2023)
Halloysite nanotube-carbonaceous (HNT-C) composites were fabricated through one-pot hydrothermal carbonization of fructose and sodium carboxymethyl cellulose for use as an adsorbent for the removal of Pb(II), Zn(II), and Cu(II) from wastewater. The composites were chemically treated with sulfuric acid after carbonization. The acidic treatment of HNT-C structures contributed to a larger specific surface area and surface functionality, which was favorable for adsorbing more metal ions. Carbonaceous-modified HNTs were characterized by elemental analysis, FT IR, XRD, and BET analysis. Metal ion adsorption experiments were conducted with solutions containing low and high total metal ion concentrations (Cu, Zn, Pb) by mixing with HNT-C composites at a solid/liquid ratio of 1.0 and 10.0 g/L. The results indicated that the HNT C composites exhibited promising Zn(II) adsorption up to 94%, while no Zn(II) adsorbed onto unmodified HNTs. The amount of Pb(II), Zn(II), and Cu(II) ions that were taken up increased as the amount of adsorbent was increased up to 10 g/L in an aqueous solution. The HNT-C composites exhibited the highest adsorption efficiency for Pb(II) ions.
Keywords: Adsorbent; adsorption; wastewater; heavy metal; halloysite nanotube